AGE OF THE OTTONE UNIT IN THE ZIGNAGO AREA (EXTERNAL LIGURIAN UNITS, NORTHERN APENNINES): CONSTRAINTS FROM CALCAREOUS NANNOFOSSILS - Catanzariti, Rita; Perilli, Nicola (Ofioliti, 2006)
Quantitative analyses of the calcareous nannofossils collected by closely spaced sampling of the Ottone Unit in the Zignago area allow to refine the age of this succession and the timing of the main steps during its tectono-sedimentary evolution. The Casanova Complex/Ottone Flysch boundary lies within the Ceratolithoides aculeus Zone (uppermost early Campanian). The sampled Ottone Flysch spans from the Ceratolithoides aculeus (uppermost early Campanian) to Quadrum gothicum Zone (early/late Campanian boundary). Sedimentation of the Mt. Veri Complex, represented by mass-gravity deposits intercalated in the Ottone Flysch, ends within the Quadrum gothicum Zone (early/late Campanian boundary). Furthermore, based on our results and on the previous ages found in the Ottone Unit successions, the lower Campanian inception of the Helminthoid Flysch sedimentation is inferred to be isochronous for the western sector of the External Ligurian Domain. The same data suggest that the end of syntectonic sedimentation of the ophiolite-bearing mass-gravity deposits occurred close the early/late Campanian boundary.